Functional traits of hyporheic and benthic invertebrates reveal importance of wood‐driven geomorphological processes in rivers. (28th June 2019) - Magliozzi, Chiara; Usseglio‐Polatera, Philippe; Meyer, Albin; Grabowski, Robert C.
Abstract: Large wood (LW) is a natural element of river environments and an integral component of many river restoration schemes to promote biodiversity. It is an important habitat in itself, but it also induces a wide range of hydraulic, hydrological, geomorphological and chemical conditions that influence the ecological community. However, the effects of hydro‐geomorphological processes induced by LW on local benthic and hyporheic invertebrates have not been well characterized. A functional approach was applied to invertebrate data collected in a field survey at sites with LW and without LW (control) to investigate the response of hyporheic and benthic invertebrates' trait profiles in response to local LW‐induced processes. We hypothesized LW sites to be associated with different trait modalities than control sites in relation to wood‐induced processes and conditions (i.e., hyporheic exchange flow, oxygen availability, temporal stability, organic matter, denitrification, hydraulic conductivity). Multivariate analyses and partial least squares (PLS) path modelling were used to detect the differences in trait profiles between LW and control sites and to study the variation of traits as a function of hydrological, sedimentological, physical and chemical variables. Biological (i.e., aquatic stages, reproduction), physiological (i.e., dispersal, feeding habits) and behavioural (i.e., substrate preferences) trait utilization by the hyporheic meiofauna differed between LW and control sites. At LW sites, the hyporheic meiofaunal assemblage was significantly associated with aquatic active dispersal, aquatic eggs and hard substrate preferences. This trait category selection was linked to changes in physical–sedimentological processes at LW sites when compared to control sites. Macrofaunal benthic and hyporheic functional traits did not differ significantly between wood and control sites, suggesting similar functioning of these assemblages at the surface–subsurface interface. This study found that LW affects invertebrate traits by altering fluvial processes to produce, locally, a mosaic of habitats. Hyporheic meiofauna trait responses to LW processes have suggested (a) the crucial role of LW in supporting river benthic zone functioning and thus (b) a possible benefit to river restoration by enhancing functional interactions among different ecological niches. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : Les bois grossiers immergés (au moins 10 cm de diamètre et 1 m de long; LW) sont des éléments naturels importants des cours d'eau, entrant dans la composition de nombreux projets de restauration visant à promouvoir la biodiversité aquatique. Habitat important en soi, un de ses avantages possibles serait sa capacité à générer une large gamme de conditions hydrauliques, hydrologiques, géomorphologiques et chimiques influençant la communauté biologique. Cependant, les effets des processus hydro‐géomorphologiques induits par les bois grossiers immergés n'ont pas été clairement mis en évidence à ce jour dans les études empiriques sur les communautés locales d'invertébrés benthiques et hyporhéiques. Une approche fonctionnelle basée sur les traits des communautés d'invertébrés benthiques et hyporhéiques collectées lors d'une campagne d'échantillonnage effectuée sur des sites avec (LW) ou sans (contrôle) bois immergés, a été réalisée afin d'examiner leurs réponses aux processus induits localement par les bois immergés. Nous avons supposé que les assemblages d'invertébrés des sites avec LW et sans LW étaient associés à des modalités de trait différentes du fait des conditions et des processus particuliers induits par les bois immergés (e.g. en termes d'échanges hyporhéiques, de disponibilité en oxygène, de stabilité temporelle, de teneur en matière organique, de niveau de dénitrification ou de conductivité hydraulique). Des approches multivariées et de modélisation PLS ont été utilisées pour (i) détecter les différences de profils de traits entre assemblages d'invertébrés dans les sites avec LW et les sites de contrôle et (ii) pour examiner les relations entre traits et variables hydrologiques, sédimentologiques, physiques et chimiques. Les traits biologiques (stades aquatiques, reproduction), physiologiques (dispersion, modes d'alimentation) et comportementaux (préférences en matière de substrat) sélectionnés par la méiofaune hyporhéique diffèrent entre sites avec LW et sites de contrôle. Dans les sites avec LW, la méiofaune hyporhéique a pu être significativement associée à une dispersion aquatique active, à la production d'œufs aquatiques et à une préférence pour des substrats grossiers, en relation avec les processus physico‐sédimentologiques opérant sur ces sites. Par contre, les traits fonctionnels de la macrofaune benthique et hyporhéique ne diffèrent pas de manière significative entre sites avec LW et sites de contrôle, suggérant un fonctionnement similaire de ces assemblages à l'interface surface/milieu hyporhéique. Notre étude a révélé que les bois immergés affectaient les traits fonctionnels des assemblages d'invertébrés du fait de la modification des processus à l'origine de la mosaïque locale d'habitats. L'analyse des réponses de la meiofaune hyporhéique en matière de traits aux processus générés par les bois immergés a démontré (i) le rôle crucial des bois immergés dans le fonctionnement de la zone benthique des cours d'eau et (ii) l'éventuel bénéfice apporté par les bois immergés lors des projets de restauration des cours d'eau, par facilitation des échanges fonctionnels entre différentes niches écologiques.